ZAMAN MELESET: BANTUL PADA MASA DEPRESI EKONOMI, 1929-1939 - Hernawati, Dhita Fitria; Wahid, Abdul (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2024)
This article discusses the social and economic conditions of Bantul Regency during the Great Depression of the 1930s. The study employed colonial reports, contemporary national and international newspapers, and secondary and tertiary sources. The researchers discovered that during this period, Bantul regency people faced numerous challenges due to the economic decline caused by this extraordinary economic disruption. The economic depression had varying impacts on different groups within Bantul society. Europeans who controlled the plantation and sugar industry, for example, experienced more significant economic hardship than indigenous society, which relied primarily on subsistence agriculture. Such different impacts led to a range of responses and strategies among the various groups as they sought to cope with the economic challenges. In response, the local government took multiple measures to support the people in overcoming the effects of the economic Depression. By examining the Bantul case, this study offers a fresh analysis of how the Economic Depression of the 1930s affected the local economy and population that previously had long been dependent on the sugar industry.